2010
DOI: 10.1109/tmi.2009.2033595
|View full text |Cite
|
Sign up to set email alerts
|

Binary Tissue Classification on Wound Images With Neural Networks and Bayesian Classifiers

Abstract: A pressure ulcer is a clinical pathology of localized damage to the skin and underlying tissue caused by pressure, shear, or friction. Diagnosis, treatment, and care of pressure ulcers are costly for health services. Accurate wound evaluation is a critical task for optimizing the efficacy of treatment and care. Clinicians usually evaluate each pressure ulcer by visual inspection of the damaged tissues, which is an imprecise manner of assessing the wound state. Current computer vision approaches do not offer a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
107
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(110 citation statements)
references
References 31 publications
2
107
0
1
Order By: Relevance
“…However, wounds evolve over time, with specific types of tissue and pigmentation with eight identifiable colors which represent healing, necrosis and/or infection. [14] This theory is also supported by observations in a recent paper by Veredas et al [15] Finally, other authors have indicated that an unaccounted color may appear in a wound bed and affect classification. [17] The current study proposes that an eight-color model would more comprehensively represent wound composition, evolution and changes due to infection.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…However, wounds evolve over time, with specific types of tissue and pigmentation with eight identifiable colors which represent healing, necrosis and/or infection. [14] This theory is also supported by observations in a recent paper by Veredas et al [15] Finally, other authors have indicated that an unaccounted color may appear in a wound bed and affect classification. [17] The current study proposes that an eight-color model would more comprehensively represent wound composition, evolution and changes due to infection.…”
Section: Introductionsupporting
confidence: 55%
“…The authors previously presented initial results showing the presence of eight tissue types and pigmentation, with a one-to-one correspondence to distinct colors. [14] Subsequently, Veredas et al, [15] in their elaborate work on pressure ulcers based on four tissue-types (with the skin regarded as the fifth), have emphasized the necessity for precise evaluation. Recently, Mukherjee et al [16] presented results using a three-color model with textures.…”
Section: Introductionmentioning
confidence: 99%
“…However, the classification error was greater than 50% for necrosis and the proposed approach required preliminary manual region of interest selection [14].…”
Section: Wound Tissue Classification Using Digital Image Analysismentioning
confidence: 95%
“…In clinical arena, assessment methods have mainly been based on Significant advances in the field of digital image processing make the standardized digital photography as the most popular tool which considers both aspects of the wound for assessment of healing. Several successful attempts to classify wound tissue have been made through segmentation algorithms applied to various sets of features extracted from different colour spaces, with the aim of objectively monitoring the colour changes during healing [8][9][10][11][12][13][14][15] and automatically determining the wound volume and area [16][17][18]. All these proposed methods for assessing wound healing provide information only at the surface level and cannot be applied to all types of wound [2,19].…”
Section: Introductionmentioning
confidence: 99%
“…Adaptability and nonlinearity of ANNs has made them well-known, easy to implement, useful tools in pattern recognition [7,8], as well as in medical image processing [9][10][11].…”
Section: Introductionmentioning
confidence: 99%